Effect of Aquaculture Wastewater And Zarrouk in Increasing Biomass, Protein, and Carotenoids levels of Spirulina platensis - Anisa Millah Taqiyyah; Yenny Risjani; Asep Awaludin Prihanto; Uun Yanuhar; Mohammad Fadjar (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research